2014
DOI: 10.1016/j.alcohol.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Operant ethanol self-administration in ethanol dependent mice

Abstract: While rats have been predominantly used to study operant ethanol self-administration behavior in the context of dependence, several studies have employed operant conditioning procedures to examine changes in ethanol self-administration behavior as a function of chronic ethanol exposure and withdrawal experience in mice. This review highlights some of the advantages of using operant conditioning procedures for examining the motivational effects of ethanol in animals with a history of dependence. As reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…This was noteworthy in light of prior studies that have found such increases (Chu et al . ; Lopez & Becker ). One critical factor accounting for these differences may be that, unlike the current study, subjects in studies where increased self‐administration was observed received exposure to CIE between test sessions.…”
Section: Discussionmentioning
confidence: 99%
“…This was noteworthy in light of prior studies that have found such increases (Chu et al . ; Lopez & Becker ). One critical factor accounting for these differences may be that, unlike the current study, subjects in studies where increased self‐administration was observed received exposure to CIE between test sessions.…”
Section: Discussionmentioning
confidence: 99%
“…However, operant testing is resource-intense with greater costs in time, materials, and technicians compared with home-cage testing. Many reviews have been written on operant procedures (June and Gilpin, 2010; Lopez and Becker, 2014; Ostroumov et al, 2015; O'Tousa and Grahame, 2014; Rodd et al, 2004b; Samson and Czachowski, 2003; Vendruscolo and Roberts, 2014; Weiss, 2011), so only the basics will be covered here. The removal of the animal from their home-cage environment, transport to a test room, and placing the animal in the operant chamber results in many opportunities for the animal to form associations between environmental stimuli and learning the reinforcement value of ethanol.…”
Section: Behavioral Models For Screening Treatment Compounds And/omentioning
confidence: 99%
“…To a great extent this is also related to the first caveat, in the sense that most of the ethanol withdrawal research has been conducted in mice. We noted some of the rat research, often using outbred rat lines, in section 4.8 and Table 8; for other work and discussion see Al’Absi (2007), Becker (2013), Burke and Miczek (2014), Greenberg and Crabbe (2016), Lopez and Becker (2014), Metten et al (2014), Phillips et al (2015), Spanagel et al (2014a), Vendruscolo and Roberts (2014), as well as Zorrilla et al (2014).…”
Section: Caveats Challenges and Conclusionmentioning
confidence: 99%
“…Although no animal model of addiction fully emulates the human condition, the existing models permit investigations of specific elements of the addiction process (Rodd et al 2004). Multiple methods have been developed to produce BALs in the 100–300 mg% range for ≥12 h per day, associated with somatic and affective withdrawal symptoms, but they use a forced alcohol liquid diet (Gilpin et al 2009; Lieber and DeCarli 1982; Overstreet et al 2004), intragastric alcohol intubation (Aujla et al 2013; Braconi et al 2010; de Guglielmo et al 2015; Sidhpura et al 2010), passive exposure to alcohol vapor (Becker and Lopez 2004; de Guglielmo et al 2016; Gilpin et al 2008; Goldstein and Pal 1971; Kallupi et al 2014; Lopez and Becker 2014; O’Dell et al 2004; Rimondini et al 2002; Roberts et al 1996; Schulteis et al 1995; Vendruscolo and Roberts 2014), or selected inbred lines of alcohol-preferring rats or mice (Bell et al 2012; Ciccocioppo et al 2006; Colombo et al 2006; Crabbe et al 2014; Matson and Grahame 2013; McBride and Li 1998; Quintanilla et al 2006; Sommer et al 2006). Forced and passive administration models have limited face validity and make it difficult to unveil the neuronal networks that mediate the voluntary induction and maintenance of alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%